Neoadjuvant plus adjuvant bevacizumab in early breast cancer (NSABP B-40 [NRG Oncology]): secondary outcomes of a phase 3, randomised controlled trial. Issue 9 (September 2015) - Bear, Harry D; Tang, Gong; Rastogi, Priya; Geyer, Charles E; Liu, Qing; Robidoux, André; Baez-Diaz, Luis; Brufsky, Adam M; Mehta, Rita S; Fehrenbacher, Louis; Young, James A; Senecal, Francis M; et al.
Summary Background NSABP B-40 was a 3 × 2 factorial trial testing whether adding capecitabine or gemcitabine to docetaxel followed by doxorubicin plus cyclophosphamide neoadjuvant chemotherapy would improve outcomes in women with operable, HER2-negative breast cancer and whether adding neoadjuvant plus adjuvant bevacizumab to neoadjuvant chemotherapy regimens would also improve outcomes. As reported previously, addition of neoadjuvant bevacizumab increased the proportion of patients achieving a pathological complete response, which was the primary endpoint. We present secondary patient outcomes, including disease-free survival, a specified endpoint by protocol, and data for distant recurrence-free interval, and overall survival, which were not prespecified endpoints but were collected prospectively. Methods In this randomised controlled trial (NSABP B-40), we enrolled women aged 18 years or older, with operable, HER2-non-amplified invasive adenocarcinoma of the breast, 2 cm or greater in diameter by palpation, clinical stage T1c–3, cN0, cN1, or cN2a, without metastatic disease and diagnosed by core needle biopsy. Patients received one of three docetaxel-based neoadjuvant regimens for four cycles: docetaxel alone (100 mg/m2) with addition of capecitabine (825 mg/m2 oral twice daily days 1–14, 75 mg/m2 docetaxel) or with addition of gemcitabine (1000 mg/m2 days 1 and 8 intravenously, 75 mg/m2 docetaxel), all followed by neoadjuvant doxorubicin and cyclophosphamide (60 mg/m2 and 600 mg/m2 intravenously) every 3 weeks for four cycles. Those randomly assigned to bevacizumab groups were to receive bevacizumab (15 mg/kg, every 3 weeks for six cycles) with neoadjuvant chemotherapy and postoperatively for ten doses. Randomisation was done (1:1:1:1:1:1) via a biased-coin minimisation procedure to balance the characteristics with respect to clinical nodal status, clinical tumour size, hormone receptor status, and age. Intent-to-treat analyses were done for disease-free survival and overall survival. This study is registered with ClinicalTrials.gov, number NCT00408408. Findings Between Jan 5, 2007, and June 30, 2010, 1206 patients were enrolled in the study. Follow-up data were collected from Oct 31, 2007 to March 27, 2014, and were available for overall survival in 1186 patients, disease-free survival in 1184, and distant recurrence-free interval in 1181. Neither capecitabine nor gemcitabine increased disease-free survival or overall survival. Median follow-up was 4·7 years (IQR 4·0–5·2). The addition of bevacizumab significantly increased overall survival (hazard ratio 0·65 [95% CI 0·49–0·88]; p=0·004) but did not significantly increase disease-free survival (0·80 [0·63–1·01]; p=0·06). Four deaths occurred on treatment due to vascular disorder (docetaxel plus capecitabine followed by doxorubicin plus cyclophosphamide group), sudden death (docetaxel plus capecitabine followed by doxorubicin plus cyclophosphamide group), infective endocarditis (docetaxel plus bevacizumab followed by doxorubicin plus cyclophosphamide and bevacizumab group), and visceral arterial ischaemia (docetaxel followed by doxorubicin plus cyclophosphamide group). The most common grade 3–4 adverse events in the bevacizumab group were neutropenia (grade 3, 99 [17%]; grade 4, 37 [6%]), hand-foot syndrome (grade 3, 63 [11%]), and hypertension (grade 3, 60 [10%]; grade 4, two [<1%]) and in the non-bevacizumab group were neutropenia (grade 3, 98 [16%]; grade 4, 36 [6%]), fatigue (grade 3, 53 [9%]), and hand-foot syndrome (grade 3, 43 [7%]). Interpretation The addition of gemcitabine or capecitabine to neoadjuvant docetaxel plus doxorubicin plus cyclophosphamide does not seem to provide any benefit to patients with operable breast cancer, and should not change clinical practice in the short term. The improved overall survival with bevacizumab contradicts the findings of other studies of bevacizumab in breast cancer and may indicate the need for additional investigation of this agent. Funding National Institutes of Health, Genentech, Roche Laboratories, Lilly Research Laboratories, and Precision Therapeutics.